TEOLOGI PENGHORMATAN - Ayub Warjianto; Fibry Jati Nugroho (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
This paper discusses relating to dialogue between Christianity and the Kembang Kuningan Rite. This rite is in the Polobogo Village area, Getasan District, Semarang Regency. Every month of the Jumadil Akhir in some “punden” (sacred tombs), a ritual is performed as part of the ceremony for the rite. The essence of the series of rituals carried out is to pray for ancestors and ask for blessings and safety for the community. Be unique when this ritual is performed by church members, who incidentally have a Christian identity, but also have an identity as a local community, using a qualitative approach and descriptive analysis method and the analysis of synthesis models. It was found that the theology of honor became a meeting point to dialogue Christian identity with the Kembang Kuningan rite